2018
DOI: 10.1177/1362361318766247
|View full text |Cite
|
Sign up to set email alerts
|

Computer vision analysis captures atypical attention in toddlers with autism

Abstract: To demonstrate the capability of computer vision analysis to detect atypical orienting and attention behaviors in toddlers with autism spectrum disorder. One hundered and four toddlers of 16-31 months old (mean = 22) participated in this study. Twenty-two of the toddlers had autism spectrum disorder and 82 had typical development or developmental delay. Toddlers watched video stimuli on a tablet while the built-in camera recorded their head movement. Computer vision analysis measured participants' attention an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
78
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(81 citation statements)
references
References 39 publications
1
78
0
2
Order By: Relevance
“…Automated emotion recognition from facial expression is an active area of research [26, 29]. In clinical contexts, investigators have detected occurrence of depression, autism, conflict, and PTSD from visual features (i.e., face and body expression or movement) [7, 10, 18, 22, 25, 27]. In the current pilot study, we explored the feasibility of detecting changes in affect in response to time-locked changes in neurophysiological challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Automated emotion recognition from facial expression is an active area of research [26, 29]. In clinical contexts, investigators have detected occurrence of depression, autism, conflict, and PTSD from visual features (i.e., face and body expression or movement) [7, 10, 18, 22, 25, 27]. In the current pilot study, we explored the feasibility of detecting changes in affect in response to time-locked changes in neurophysiological challenge.…”
Section: Introductionmentioning
confidence: 99%
“…For example, ASD patients apparently perform better than usual in some visual tasks, and worse in others [19]. It has also been shown that certain types of visual stimulus, such as computer screen lights, capture the attention of individuals affected by ASD more than would be expected for neurotypical people [20]. Additionally, because the retina is part of the central nervous system (CNS), it uses mainly glutamate and GABA to transmit and modulate visual signals [21] and produces most, if not all, neurotransmitters found in the brain.…”
mentioning
confidence: 99%
“…Concerning the assessment of ASD behavioral cues, computer vision and machine learning techniques have been effectively exploited in the last years to highlight signs that are considered early features of ASD [12]. Computer vision analysis measured participants' attention and orienting in response to name calls in [13] whereas in [14] the head postural stability was evaluated while the children watched a series of dynamic movies involving different types of stimuli. Both works made use of an algorithm that detects and tracks 49 facial landmarks on the child's face and estimates head pose angles relative to the camera by computing the optimal rotation parameters between the detected landmarks and a 3D canonical face model.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, from the last column, it is possible to derive that works in [19][20][21][22] did not consider any quantitative evaluation but just a qualitative analysis of the outcomes to highlight the differences in affective abilities of ASD vs. TD groups. [16] x x x expert clinician [15] x manual annotation [13] x x human rater [14] x ASD vs. TD [19] x ASD vs. TD [20] x ASD vs. TD [21] x ASD vs. TD [22] x ASD vs. TD [24] x diagnostic labels (ASD/non-ASD) [23] x x expert human raters (smiling/not smiling)) [8] x expert psychologists (only on ASD Group)…”
Section: Related Workmentioning
confidence: 99%